DEVELOPMENT AND PHYSICOCHEMICAL CHARACTERIZATION OF AN ECO-FRIENDLY BODY SCRUB FROM AVOCADO PEEL (Persea americana Mill.) - Inas Dayini Febrianty; Dyan Wigati (Jurnal Jamu Kusuma, 2026)
Continuous exposure to sunlight, environmental pollutants, and daily activities can adversely affect skin health, increasing the demand for effective skincare products. Body scrubs formulated with natural ingredients have gained considerable attention due to their exfoliating and antioxidant properties. Avocado (Persea americana Mill.) peel, an agricultural by-product, is rich in bioactive compounds with potential applications in cosmetic formulations. This study aimed to develop a body scrub containing avocado peel powder and evaluate its physicochemical characteristics, skin hydration effect, and consumer acceptability. An experimental laboratory study was conducted to formulate body scrubs incorporating avocado peel powder at varying concentrations. The formulations consisting of F0 (0%), F1 (2.5%), F2 (5.0%), and F3 (7.5%) avocado peel powder (Persea americana Mill.) were evaluated for organoleptic properties, homogeneity, spreadability, and pH. Skin hydration was measured before and after four weeks of product application, while consumer acceptability was assessed through a hedonic test involving trained panelists. All formulations demonstrated acceptable physicochemical characteristics, including uniform appearance, good homogeneity, appropriate spreadability, and pH values compatible with skin physiology. Significant improvements in skin hydration were observed across all formulations after four weeks of regular use. Among the tested formulations, Formula 1 (F1) received the highest hedonic scores, indicating the greatest level of panelist preference. Conclusion: Avocado peel powder exhibits promising potential as a natural exfoliating agent in body scrub formulations. The developed products possessed satisfactory physicochemical properties, enhanced skin hydration, and received high consumer acceptance, supporting the valorization of avocado peel as a sustainable and value-added ingredient in cosmetic applications.